'Characterisation of suspected Crimean-Congo Haemorrhagic Fever (CCHF) cases in a public sector hospital Islamabad'. Issue 1 (1st January 2020) - Noreen, Nadia; Saima, Dil; Irum, Naveed; Asghar, Rana Jawad; Faiz, Asad Ullah; Mohiuddin, Naseer; Ali Khan, Mumtaz; Ullah Khan, Naveed; Khudaidad, Farida; Khalid Khan, Fawad
ABSTRACT: Pakistan has been experiencing a continuous rise in the incidence of Crimean Congo Haemorrhagic Fever (CCHF). Sporadic cases of CCHF are reported from rural areas of Punjab, Azad Jammu Kashmir and Khyber Pakhtunkhwa and neighbouring Afghanistan where cattle herding is common. The objective of this paper was to describe the epidemiology of CCHF. A descriptive study was carried out in the CCHF isolation ward in Islamabad in a tertiary care hospital from February to November 2018. Using a standardised case definition, all patients admitted in the isolation ward with clinical evidence of CCHF were included in the study. After taking the informed consent, data were collected on demographic factors, history of animal contact, tick-bite history, co-morbidity, laboratory results and treatment outcome. Data were analysed as per time, place and person. During the study period, 40 suspected CCHF patients were admitted in the isolation ward, 32 (80%) males were affected. Mean age of the cases was 33.5 years (range 13–70 years). Most affected 17 (42.5%) age group was 20–29 years. Animal contact history was found in Thirty-seven (92.5%) of cases and 28 (70%) with tick bites. Most of the cases, 26 (65%), were reported from July to August. Forty patients in this study were tested by Real Time Polymerase Chain Reaction (PCR), 20 (50%) were positive, out of which 6(30%) expired. Majority of the positive patients were animal handlers by occupation (37.5%). Proper personal protective equipment was available. The reference laboratory facility was not available for immediate investigations was sent to National Institute of Health for confirmation. The overall results show the important risk factors for CCHF a history of tick bites, high-risk occupations and having contact with livestock. Public health measures should focus on preventing tick bites, increasing awareness of CCHF signs and symptoms, timely investigation, and treatment to reduce mortality. Our analyses recommend the government to set up isolation units in all major hospitals, and proper surveillance system.